Integration of Physical Education and Health Promotion Background The Value of Taijiquan to National Fitness and Its Development Path - Zhao, Zikun; Xu, Aie; Zhao, Jiajia (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details